C103. Pathogenesis, Biomarkers, and Risk Factors for Interstitial Lung Disease: From Bench to Bedside 2012
DOI: 10.1164/ajrccm-conference.2012.185.1_meetingabstracts.a5183
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Among African American Women With Sarcoidosis: Data From The Black Women's Health Study

Abstract: Rationale Sarcoidosis is a chronic systemic granulomatous disease of unknown etiology that disproportionately affects black females. Few studies have specifically addressed causes of death in this population. Objectives To assess rates and causes of death among women with sarcoidosis in a prospective cohort study of U.S. black women. Methods The Black Women’s Health Study is a follow-up study of 59,000 U.S. black women aged 21–69 (median age 38) at entry in 1995. Data on demographic and lifestyle factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 12 publications
(23 reference statements)
1
31
2
Order By: Relevance
“…This is in contrast to previous reports that observed an approximately 2-fold increased rate of mortality (4, 10). This discrepancy may reflect differences in management of sarcoidosis in different regions or the difference of severity and outcome of sarcoidosis across ethnic groups (11, 12).…”
Section: Epidemiology Of Sarcoidosiscontrasting
confidence: 99%
“…This is in contrast to previous reports that observed an approximately 2-fold increased rate of mortality (4, 10). This discrepancy may reflect differences in management of sarcoidosis in different regions or the difference of severity and outcome of sarcoidosis across ethnic groups (11, 12).…”
Section: Epidemiology Of Sarcoidosiscontrasting
confidence: 99%
“…The authors evaluated sarcoidosis-related mortality compared with the general population, the impact of the most prevalent sarcoidosis-related comorbid conditions, and geographical differences within France. They found that deaths were higher and at younger ages among sarcoidosis patients than among the general population, confirming previous findings from the USA [25,26]. Women died less frequently than men, but the average age at death was similar for both sexes.…”
supporting
confidence: 77%
“…This is in contrast to the report of a significant increase in the mortality rate from a British population-based study, with hazard ratio of 2.09 (95% CI, 1.59–2.74), 14 and an African-American female prospective cohort study, with hazard ratio of 2.44 (95% CI, 2.03–2.93). 23 This discrepancy may reflect differences in management in different geographical regions or the difference of sarcoidosis severity among different ethnic groups. For example, a coding-based study using the U.S. death certificates demonstrated that the age-adjusted mortality rates differed by sex and ethnic groups.…”
Section: Discussionmentioning
confidence: 99%